BIODIVERSITY OF FISH SPECIES IN ERE RIVER, ADO-ODO AXIS OF OGUN STATE, NIGERIA. - Adeboyejo, O. A; Okunade, M. K.; Adaramoye, O. R. (Nigerian Journal of Fisheries, 2020)
The purpose of this study is to determine fish species biodiversity in Ere River. Monthly collection of Fishes from fishermen was from March to August 2018. A total of 626 fish species were studied. Biodiversity indices were determined using: Simpson’s index (d), Reciprocal index (I/d) and index of diversity (I-d). Water samples were collected randomly at different fishing spots on the river bi-monthly for six months for Physico-chemical analyses: temperature (℃), pH, total dissolved solids (mg/L), and conductivity (μs/cm) were conducted in-situ using HANNA multi-parametric meter (Hi 98129). While Dissolved Oxygen, Nitrate, Phosphate, Alkalinity and Hardness (mg/l) were determined ex-situ using standard methods. Fish species percentage composition is 8 families, 8 genera and 10 species including Oreochromis niloticus, Tilapia zilli, and Sarotherodon galileaus, Papyrocranus afer (42%), Heterotis niloticus, and Parachanna obscura(8%), Chrysichthys nigrodigitatus (9%), Clarias gariepinus (10%), Calamoichthys calabaricus (7%), and Gymnarchus niloticus (5%). Simpsons index (d) was 0.201, Reciprocal index (I/d) was 4.975 and the index of diversity (I-d) had 0.799. The Evenness (E) was 0.2336 and Shannon Weiner index (H) 1.804. Physico-chemical parameters and heavy metal content of the water were within the WHO recommended limit for adequate fishing. The study recommends better management of the fisheries.